Extrarenal renal cell carcinoma in the adrenal region: a case report - Yao, Kai; Huang, Long; Zhang, Jing Li; Xu, Yan; Liu, Dong Liang (Frontiers in Surgery, 2024)
This case report describes a rare instance of extrarenal clear cell renal cell carcinoma (ccRCC) in a 48-year-old woman who presented with a loss of consciousness. Abdominal CT revealed a 24 × 31 mm mass in the left adrenal region, with no kidney involvement. The mass was surgically excised, and histopathological examination confirmed the diagnosis of ccRCC. Immunohistochemical analysis revealed positive markers, including CA9, CD10, PAX-8, and vimentin. The patient did not undergo adjuvant therapy, and a 6-month follow-up showed no signs of recurrence or metastasis. This case emphasizes the importance of considering extrarenal ccRCC in differential diagnoses of adrenal masses.